Authenticating the geographic origins of Atractylodes lancea rhizome chemotypes in China through metabolite marker identification - Zhang, Chengcai; Wang, Hongyang; Lyu, Chaogeng; Wang, Yiheng; Sun, Jiahui; Zhang, Yan; Xiang, Zengxu; Guo, Xiuzhi; Wang, Yuefeng; Qin, Ming; Wang, Sheng; Guo, Lanping (Frontiers in Plant Science, 2023)
Introduction Atractylodes lancea is widely distributed in East Asia, ranging from Amur to south-central China. The rhizome of A. lancea is commonly used in traditional Chinese medicine, however, the quality of products varies across different regions with different geochemical characteristics. Method This study aimed to identify the chemotypes of A. lancea from different areas and screen for chemical markers by quantifying volatile organic compounds (VOCs) using a targeted metabolomics approach based on GC–MS/MS. Results The A. lancea distributed in Hubei, Anhui, Shaanxi, and a region west of Henan province was classified as the Hubei Chemotype (HBA). HBA is characterized by high content of β-eudesmol and hinesol with lower levels of atractylodin and atractylon. In contrast, the Maoshan Chemotype (MA) from Jiangsu, Shandong, Shanxi, Hebei, Inner Mongolia, and other northern regions, exhibited high levels of atractylodin and atractylon. A total of 15 categories of VOCs metabolites were detected and identified, revealing significant differences in the profiles of terpenoid, heterocyclic compound, ester, and ketone among different areas. Multivariate statistics indicated that 6 compounds and 455 metabolites could serve as candidate markers for differentiating A. lancea obtained from the southern, northern, and Maoshan areas. Discussion This comprehensive analysis provides a chemical fingerprint of selected A. lancea. Our results highlight the potential of metabolite profiling combined with chemometrics for authenticating the geographical origin of A. lancea.